RATAAN BOBOT SAPIH DAN PERTAMBAHAN BOBOT BADAN DOMBA GARUT DARI LEPAS SAPIH HINGGA UMUR 8 BULAN DI UPTD BPPTDK MARGAWATI 2014-2016 - Haitsam Muthi Praja; An An Nurmeidiansyah; Denie Heriyadi (Jurnal Produksi Ternak Terapan, 2020)
The first step to the process of Garut Sheep development can be started by selection, which is an action to select livestock that is considered good and has the genetic potential to be developed further. The weights of weaning weight and the increase of body weight can be used as a parameter for selection because it is considered to have high economic value so that it can be a determinant of productivity level. The purpose of this research is to know the average of weaning and daily gain. The research was conducted at UPTD BPPTDK Margawati on 21-27 August 2017. The object of research used was Garut sheep from weaning to 8 months old. The research method used a retrospective descriptive method with data collection conducted by purposive sampling. Based on the results and discussion can be concluded that the average weight of wean Garut Sheep at UPTD BPPTDK Margawati in 2014-2016 is 11.56±2.15 kilogram. The average weight gain Garut Sheep from weaning up to age 8 months in UPTD BPPTDK Margawati in 2014-2016 is 45.85±8.15 gram/head/day.